Novel 7XXX aluminum alloy product
By introducing customized microstructures and appropriate amounts of Zr into the 7xxx aluminum alloy, a combination of improved strength, ductility and fracture toughness is formed, and the problem of difficulty in maintaining the strength improvement of 7xxx aluminum alloy in the prior art is solved, and the material performance is achieved Comprehensive improvement.
Patent Information
- Application Number
- CN202380043224.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-17
- Filing Date
- 2023-05-16
- Publication Date
- 2025-01-07
AI Technical Summary
The existing 7xxx aluminum alloys are difficult to maintain fracture toughness and corrosion resistance while increasing their strength, and are prone to corrosion.
By introducing custom microstructures in 7xxx aluminum alloys, including 10% to 40% recrystallization grains and appropriate grain sizes, combined with appropriate amounts of Zr and other anti-recrystallization agents, the particles stimulate nucleation and form with improved strength , combination of ductility and fracture toughness.
It is achieved to significantly improve the strength and fracture toughness of 7xxx aluminum alloy without reducing other characteristics, improve its microstructure, and enhance the overall performance of the material.
Smart Images

Figure BDA0005155643620000131 
Figure BDA0005155643620000132 
Figure BDA0005155643620000161
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This patent application claims priority to U.S. Provisional Patent Application No. 63 / 343,074, filed on May 17, 2022, entitled “NEW 7XXX ALUMINUM ALLOY PRODUCTS,” which is incorporated herein by reference in its entirety. Background Art
[0003] Aluminum alloys are useful in a variety of applications. However, it is elusive to improve one property of an aluminum alloy without reducing another property. For example, it is difficult to improve the strength of a wrought aluminum alloy without affecting other properties such as fracture toughness or corrosion resistance. 7xxx (based on Al-Zn-Mg) is susceptible to corrosion. See, for example, Bonn, W. Gruhl, "The stress corrosion behavior of high strength AIZnMg alloys", paper published at the International Meeting of Associazione Italiana di Metallurgie, "Aluminum Alloys in Aircraft Industries", Turin, October 1976.
[0004] One U.S. patent that describes the AA7050 alloy is U.S. Patent No. 7,135,077. This patent describes an alloy with a "slightly recrystallized microstructure" and a "high cast grain size" that "may result in a particular microstructure of the transformed and heat treated product that has a beneficial effect on toughness without compromising strength or other properties." Summary of the invention
[0005] In summary, the present patent application relates to a new 7xxx aluminum alloy product having an improved combination of properties, such as an improved combination of strength, ductility, and fracture toughness. The improved combination of properties can be attributed to, for example, a new 7xxx aluminum alloy having a tailored microstructure. For example, the new 7xxx aluminum alloy can include 10% to 40% recrystallized grains. In one embodiment, at least some of the recrystallized grains are located at the periphery of unrecrystallized grains. In one embodiment, the recrystallized grains are obtained at least in part due to: (i) the use of no more than 0.11 wt. % Zr (or other anti-recrystallization agent) in the 7xxx aluminum alloy product; (ii) particle stimulated nucleation; or (iii) both. The improved combination of properties can be at least in part due to the new 7xxx aluminum alloy product having an appropriate grain size, such as an average grain size (d-bar) of at least 300 microns, where the average grain size is an area-weighted average circular equivalent diameter grain size. In one embodiment, the new 7xxx aluminum alloy product includes a tailored amount of recrystallized regions relative to the average grain size of the new 7xxx aluminum alloy product. In one embodiment, a new 7xxx aluminum alloy product achieves an ID:d-bar ratio of 0.5 to 2.0, wherein the ID:d-bar ratio is the ratio of (A) the average intercept (ID) to (B) the average grain size (d-bar) of the 7xxx aluminum alloy product. For purposes of calculating this ratio, the average intercept (ID) is the average distance between recrystallized regions of the 7xxx aluminum alloy product. Methods for determining the average grain size (d-bar) and intercept, as well as other microstructural features, are described in the microstructural evaluation procedure described below.
[0006] i. Composition
[0007] The new 7xxx aluminum alloy product can be any 7xxx aluminum alloy suitable for improvement by having a tailored microstructure as described herein. The new 7xxx aluminum alloy typically includes 5 wt % to 10 wt % Zn, 1 wt % to 3 wt % Mg, and 1 wt % to 3 wt % Cu, etc. In one embodiment, the new 7xxx aluminum alloy includes other minor alloying additions, such as manganese (e.g., 0.05 wt % to 0.60 wt % Mn).
[0008] In one embodiment, the new 7xxx aluminum alloy product may contain a low amount of recrystallization inhibitors, such as a low amount of zirconium, to promote partial recrystallization of the new 7xxx aluminum alloy product. In one embodiment, the new 7xxx aluminum alloy product may contain no more than 0.11 wt % Zr, such as 0.01 wt % to 0.11 wt % Zr. In one embodiment, the new 7xxx aluminum alloy product contains no more than 0.10 wt % Zr. In another embodiment, the new 7xxx aluminum alloy product contains no more than 0.09 wt % Zr. In yet another embodiment, the new 7xxx aluminum alloy product contains no more than 0.08 wt % Zr. In another embodiment, the new 7xxx aluminum alloy product contains no more than 0.07 wt % Zr.
[0009] In one embodiment, the new 7xxx aluminum alloy product includes at least 0.03 wt. % Zr. In another embodiment, the new 7xxx aluminum alloy product includes at least 0.04 wt. % Zr. In yet another embodiment, the new 7xxx aluminum alloy product includes at least 0.05 wt. % Zr. In another embodiment, the new 7xxx aluminum alloy product includes at least 0.06 wt. % Zr. In yet another embodiment, the new 7xxx aluminum alloy product includes at least 0.07 wt. % Zr.
[0010] As described above, the new 7xxx aluminum alloy may include 0.05 wt. % to 0.60 wt. % Mn. In one embodiment, the 7xxx aluminum alloy includes at least 0.08 wt. % Mn. In another embodiment, the new 7xxx aluminum alloy includes at least 0.10 wt. % Mn. In yet another embodiment, the new 7xxx aluminum alloy includes at least 0.12 wt. % Mn. In another embodiment, the new 7xxx aluminum alloy includes at least 0.15 wt. % Mn. In yet another embodiment, the new 7xxx aluminum alloy includes at least 0.18 wt. % Mn. In another embodiment, the new 7xxx aluminum alloy includes at least 0.20 wt. % Mn. In yet another embodiment, the new 7xxx aluminum alloy includes at least 0.22 wt. % Mn. In another embodiment, the new 7xxx aluminum alloy includes at least 0.25 wt. % Mn.
[0011] In one embodiment, the 7xxx aluminum alloy includes no more than 0.55 wt % Mn. In another embodiment, the 7xxx aluminum alloy includes no more than 0.50 wt % Mn. In yet another embodiment, the 7xxx aluminum alloy includes no more than 0.45 wt % Mn. In another embodiment, the 7xxx aluminum alloy includes no more than 0.40 wt % Mn. In yet another embodiment, the 7xxx aluminum alloy includes no more than 0.35 wt % Mn. In another embodiment, the 7xxx aluminum alloy includes no more than 0.30 wt % Mn. In yet another embodiment, the 7xxx aluminum alloy includes no more than 0.28 wt % Mn.
[0012] In some embodiments, the new 7xxx aluminum alloys are Mn-free and contain less than 0.05 wt. % Mn.
[0013] The new 7xxx aluminum alloy product may include up to 0.20 wt % Cr. In one approach, the 7xxx aluminum alloy includes 0.05 wt % to 0.20 wt % Cr. In another approach, the 7xxx aluminum alloy includes no more than 0.15 wt % Cr. In one embodiment, the 7xxx aluminum alloy includes no more than 0.10 wt % Cr. In another embodiment, the 7xxx aluminum alloy includes no more than 0.08 wt % Cr. In yet another embodiment, the 7xxx aluminum alloy includes no more than 0.05 wt % Cr. In another embodiment, the 7xxx aluminum alloy includes no more than 0.04 wt % Cr. In yet another embodiment, the 7xxx aluminum alloy includes no more than 0.03 wt % Cr. In another embodiment, the 7xxx aluminum alloy includes no more than 0.02 wt % Cr. In yet another embodiment, the 7xxx aluminum alloy includes no more than 0.01 wt % Cr. In another embodiment, the 7xxx aluminum alloy includes no more than 0.005 wt % Cr.
[0014] The new 7xxx aluminum alloy products may include up to 0.20 wt % V. In one approach, the 7xxx aluminum alloy includes 0.05 wt % to 0.20 wt % V. In another approach, the 7xxx aluminum alloy includes no more than 0.15 wt % V. In one embodiment, the 7xxx aluminum alloy includes no more than 0.10 wt % V. In another embodiment, the 7xxx aluminum alloy includes no more than 0.08 wt % V. In yet another embodiment, the 7xxx aluminum alloy includes no more than 0.05 wt % V. In another embodiment, the 7xxx aluminum alloy includes no more than 0.04 wt % V. In yet another embodiment, the 7xxx aluminum alloy includes no more than 0.03 wt % V. In another embodiment, the 7xxx aluminum alloy includes no more than 0.02 wt % V. In yet another embodiment, the 7xxx aluminum alloy includes no more than 0.01 wt % V. In another embodiment, the 7xxx aluminum alloy includes no more than 0.005 wt % V.
[0015] The new 7xxx aluminum alloy products may include up to 0.20 wt % Fe. In one embodiment, the 7xxx aluminum alloy includes at least 0.01 wt % Fe. In another embodiment, the 7xxx aluminum alloy includes at least 0.03 wt % Fe. In yet another embodiment, the 7xxx aluminum alloy includes at least 0.05 wt % Fe. In another embodiment, the 7xxx aluminum alloy includes at least 0.07 wt % Fe. In yet another embodiment, the 7xxx aluminum alloy includes at least 0.09 wt % Fe.
[0016] In one embodiment, the 7xxx aluminum alloy comprises no more than 0.18 wt % Fe. In another embodiment, the 7xxx aluminum alloy comprises no more than 0.16 wt % Fe. In yet another embodiment, the 7xxx aluminum alloy comprises no more than 0.14 wt % Fe. In another embodiment, the 7xxx aluminum alloy comprises no more than 0.12 wt % Fe. In some embodiments, iron is limited to a fairly low level, which may help improve bending properties. In one embodiment, the 7xxx aluminum alloy comprises no more than 0.10 wt % Fe. In another embodiment, the 7xxx aluminum alloy comprises no more than 0.08 wt % Fe. In yet another embodiment, the 7xxx aluminum alloy comprises no more than 0.06 wt % Fe. In another embodiment, the 7xxx aluminum alloy comprises no more than 0.05 wt % Fe. In yet another embodiment, the 7xxx aluminum alloy comprises no more than 0.04 wt % Fe.
[0017] The new 7xxx aluminum alloy products may include up to 0.15 wt. % Si. In one embodiment, the 7xxx aluminum alloy includes at least 0.01 wt. % Si. In another embodiment, the 7xxx aluminum alloy includes at least 0.03 wt. % Si. In yet another embodiment, the 7xxx aluminum alloy includes at least 0.05 wt. % Si.
[0018] In one embodiment, the 7xxx aluminum alloy comprises no more than 0.12 wt % Si. In another embodiment, the 7xxx aluminum alloy comprises no more than 0.10 wt % Si. In yet another embodiment, the 7xxx aluminum alloy comprises no more than 0.08 wt % Si. In some embodiments, silicon is limited to a fairly low level, which may help improve bending properties. In one embodiment, the 7xxx aluminum alloy comprises no more than 0.07 wt % Si. In another embodiment, the 7xxx aluminum alloy comprises no more than 0.06 wt % Si. In yet another embodiment, the 7xxx aluminum alloy comprises no more than 0.05 wt % Si. In another embodiment, the 7xxx aluminum alloy comprises no more than 0.04 wt % Si. In yet another embodiment, the 7xxx aluminum alloy comprises no more than 0.03 wt % Si.
[0019] The new 7xxx aluminum alloy products may include up to 0.15 wt. % Ti. In one embodiment, the 7xxx aluminum alloy includes at least 0.005 wt. % Ti. In another embodiment, the 7xxx aluminum alloy includes at least 0.01 wt. % Ti. In yet another embodiment, the 7xxx aluminum alloy includes at least 0.015 wt. % Ti. In another embodiment, the 7xxx aluminum alloy includes at least 0.020 wt. % Ti. In yet another embodiment, the 7xxx aluminum alloy includes at least 0.025 wt. % Ti.
[0020] In one embodiment, the 7xxx aluminum alloy includes no more than 0.12 wt. % Ti. In another embodiment, the 7xxx aluminum alloy includes no more than 0.10 wt. % Ti. In yet another embodiment, the 7xxx aluminum alloy includes no more than 0.08 wt. % Ti. In yet another embodiment, the 7xxx aluminum alloy includes no more than 0.05 wt. % Ti.
[0021] The new 7xxx aluminum alloy generally comprises the alloy composition, and the balance is aluminum, optional incidental elements (incidental element) and impurities. As used herein, "incidental elements" refer to elements or materials that can be optionally added to the alloy to help alloy production in addition to the elements listed above. Examples of incidental elements include casting aids, such as deoxidizers. Optional incidental elements can be included in the alloy in an accumulated amount of up to 1.0 weight %. As a non-limiting example, one or more incidental elements can be added to the alloy during casting to reduce or limit (and in some cases, eliminate) ingot cracking caused by, for example, oxide folding, pits and oxide patches. These types of incidental elements are generally referred to as deoxidizers in this article. Examples of some deoxidizers include Ca, Sr and Be. When calcium (Ca) is included in the alloy, it is generally present in an amount of up to about 0.05 weight % or up to about 0.03 weight %. In some embodiments, the amount of Ca included in the alloy is about 0.001 wt % to 0.03 wt % or about 0.05 wt %, such as 0.001 wt % to 0.008 wt % (or 10 to 80 ppm). Strontium (Sr) may be included in the alloy as a substitute for Ca (completely or partially), and therefore may be included in the alloy in the same or similar amount as Ca. Traditionally, the addition of beryllium (Be) helps to reduce the tendency of ingot cracking, but for environmental, health and safety reasons, some embodiments of the alloy are substantially free of Be. When Be is included in the alloy, it is generally present in an amount of up to about 20 ppm. The incidental element may be present in trace amounts, or may be present in large amounts, and may add desired or other features by itself without departing from the alloy described herein, as long as the alloy maintains the desired features described herein. However, it should be understood that the scope of the present disclosure may not be circumvented by only adding one or more elements of the amount that will not otherwise affect the desired and obtained characteristic combinations herein.
[0022] The new 7xxx aluminum alloy may contain a small amount of impurities. In one embodiment, the new 7xxx aluminum alloy includes impurities totaling no more than 0.15 wt %, and each impurity wherein the aluminum alloy includes no more than 0.05 wt %. In another embodiment, the new 7xxx aluminum alloy includes impurities totaling no more than 0.10 wt %, and each impurity wherein the aluminum alloy includes no more than 0.03 wt %.
[0023] In one embodiment, the new 7xxx aluminum alloy product has a composition consistent with AA7050, wherein the AA7050 consistent alloy may include 0 wt % to 0.11 wt % Zr. That is, the new 7xxx aluminum alloy product has a composition consistent with conventional AA7050, but includes 0 wt % to 0.11 wt % Zr, as opposed to the amounts typically specified for AA7050. AA7150 may also be used and appropriately modified to have 0 wt % to 0.11 wt % Zr.
[0024] In another embodiment, a new 7xxx aluminum alloy product has a composition consistent with AA7x40, wherein the AA7x40 consistent alloy may include 0 wt % to 0.11 wt % Zr. That is, the new 7xxx aluminum alloy product has a composition consistent with a conventional AA7x40 alloy, but includes 0 wt % to 0.11 wt % Zr, as opposed to the amount typically specified for AA7x40 alloys. As used herein, AA7x40 alloys include 7040 and 7140 as well as other alloys that may be registered under the 7x40 designation.
[0025] In another embodiment, a new 7xxx aluminum alloy product has a composition consistent with AA7x85, wherein the AA7x85 consistent alloy may include 0 wt % to 0.11 wt % Zr. That is, the new 7xxx aluminum alloy product has a composition consistent with a conventional AA7x85 alloy, but includes 0 wt % to 0.11 wt % Zr, as opposed to the amount typically specified for AA7x85 alloys. As used herein, AA7x85 alloys include 7085 and 7185 as well as other alloys that may be registered under the 7x85 designation.
[0026] In another embodiment, a new 7xxx aluminum alloy product has a composition consistent with AA7x65, wherein the AA7x65 consistent alloy may include 0 wt % to 0.11 wt % Zr. That is, the new 7xxx aluminum alloy product has a composition consistent with a conventional AA7x65 alloy, but includes 0 wt % to 0.11 wt % Zr, as opposed to the amount typically specified for AA7x65 alloys. As used herein, AA7x65 alloys include 7065 and other alloys that may be registered under the 7x65 designation.
[0027] In another embodiment, a new 7xxx aluminum alloy product has a composition consistent with AA7x99, wherein the AA7x99 consistent alloy may include 0 wt % to 0.11 wt % Zr. That is, the new 7xxx aluminum alloy product has a composition consistent with a conventional AA7x99 alloy, but includes 0 wt % to 0.11 wt % Zr, as opposed to the amount typically specified for AA7x99 alloys. As used herein, AA7x99 alloys include 7099 and 7199 as well as other alloys that may be registered as 7x99 designations.
[0028] In one embodiment, the new 7xxx aluminum alloy has a composition according to commonly owned U.S. Patent Application Publication No. 2017 / 0088920, i.e., the new 7xxx aluminum alloy includes 6.0 wt. % to 10.0 wt. % Zn, 1.3 wt. % to 2.3 wt. % Mg, and 1.2 wt. % to 2.6 wt. % Cu, up to 0.50 wt. % Mn; up to 0.15 wt. % Zr; up to 0.15 wt. % Ti; up to 0.15 wt. % Si; and up to 0.15 wt. % Fe, with the balance being aluminum and other elements, wherein the wrought 7xxx aluminum alloy product includes no more than 0.05 wt. % of any other element, and wherein the wrought 7xxx aluminum alloy product includes no more than 0.15 wt. % other elements in total. The disclosure of U.S. Patent Application Publication No. 2017 / 0088920 relates to the composition of the 7xxx aluminum alloy, which is incorporated herein by reference.
[0029] In one embodiment, the new 7xxx aluminum alloy has a composition according to commonly owned U.S. Patent Application Publication No. 2020 / 0115780, i.e., the new 7xxx aluminum alloy includes 0.15 wt. % to 0.50 wt. % Mn and 5.5 wt. % to 7.5 wt. % Zn, 0.95 wt. % to 2.20 wt. % Mg, and 1.50 wt. % to 2.40 wt. % Cu, with the balance being aluminum, normal grain structure control materials, grain refiners, and impurities, such as one or more of Zr, Cr, Sc, and Hf as grain structure control materials (e.g., one or more of Zr, Cr, Sc, and Hf each accounting for 0.05 wt. % to 0.25 wt. %), which limits the total amount of these elements so that large primary particles are not formed in the alloy, up to 0.15 wt. % Ti as a grain refiner, optionally with some titanium in the form of TiB2 and / or TiC. Up to 0.20 wt. % Fe and up to 0.15 wt. % Si as impurities. The disclosure of U.S. Patent Application Publication No. 2020 / 0115780, which is incorporated herein by reference, relates to the composition of 7xxx aluminum alloys.
[0030] In another embodiment, the new 7xxx aluminum alloy has a composition according to commonly owned U.S. Patent Application Publication No. 2021 / 0340656, i.e., the new 7xxx aluminum alloy contains 0.05 wt.% to 1.0 wt.% Ag; 5.5 wt.% to 9.0 wt.% Zn; 1.2 wt.% to 2.6 wt.% Cu; 1.3 wt.% to 2.5 wt.% Mg; up to 0.60 wt.% Mn; up to 1.0 wt.% of at least one grain structure controlling material, wherein the at least one grain structure controlling material is selected from Zr, Cr, V, Hf, other rare earth elements and combinations thereof; up to 0.15 wt.% Ti; up to 0.20 wt.% Fe; up to 0.15 wt.% Si; no more than 0.08 wt.% Sc; and no more than 0.05 wt.% Li, with the balance being aluminum, optional incidental elements, and impurities. The disclosure of U.S. Patent Application Publication No. 2021 / 0340656 relates to the composition of 7xxx aluminum alloys, which is incorporated herein by reference.
[0031] In another embodiment, the new 7xxx aluminum alloy has a composition according to commonly owned U.S. Patent Application Publication No. 2022 / 0106672, i.e., the new 7xxx aluminum alloy includes 5.5 wt. % to 6.5 wt. % Zn, 1.7 wt. % to 2.3 wt. % Cu, 1.3 wt. % to 1.7 wt. % Mg, the balance being aluminum, normal grain structure control materials, grain refiners, and impurities, such as one or more of Zr, Cr, Sc, and Hf as grain structure control materials (e.g., one or more of Zr, Cr, Sc, and Hf each accounting for 0.05 wt. % to 0.25 wt. %), which limits the total amount of these elements so that large primary particles are not formed in the alloy, less than 0.15 wt. % Mn; up to 0.15 wt. % Ti as a grain refiner, optionally some titanium in the form of TiB2 and / or TiC, and up to 0.20 wt. % Fe and up to 0.15 wt. % Si as impurities. The disclosure of U.S. Patent Application Publication No. 2022 / 0106672 relates to the composition of 7xxx aluminum alloys, which is incorporated herein by reference.
[0032] The new 7xxx aluminum alloys are generally substantially free of lithium, i.e., lithium is included only as an impurity, and is generally less than 0.04 wt % Li, or less than 0.01 wt % Li. The new 7xxx aluminum alloys are generally substantially free of silver, i.e., silver is included only as an impurity, and is generally less than 0.04 wt % Ag, or less than 0.01 wt % Ag. The new 7xxx aluminum alloys are generally substantially free of lead, i.e., lead is included only as an impurity, and is generally less than 0.04 wt % Pb, or less than 0.01 wt % Pb. The new 7xxx aluminum alloys are generally substantially free of cadmium, i.e., cadmium is included only as an impurity, and is generally less than 0.04 wt % Cd, or less than 0.01 wt % Cd. The new 7xxx aluminum alloys are generally substantially free of thallium, i.e., thallium is included only as an impurity, and is generally less than 0.04 wt % Tl, or less than 0.01 wt % Tl. The new 7xxx aluminum alloys are typically substantially free of scandium, i.e., scandium is included only as an impurity, and typically less than 0.04 wt. % Sc, or less than 0.01 wt. % Sc. The new 7xxx aluminum alloys are typically substantially free of nickel, i.e., nickel is included only as an impurity, and typically less than 0.04 wt. % Ni, or less than 0.01 wt. % Ni.
[0033] ii. Production method
[0034] The new 7xxx aluminum alloys can be produced as ingots or strips by casting (e.g., direct cold casting or continuous casting) and then appropriately processed to achieve various tempers, such as one of the T temper, W temper, O temper, or F temper according to ANSI H35.1 (2009). In one embodiment, the new aluminum alloy is processed into a "T temper" (heat treatment), such as any of the T1, T2, T3, T4, T5, T6, T7, T8, T9, or T10 tempers according to ANSI H35.1 (2009). Among them, the T6 and T7 tempers may be particularly relevant.
[0035] For example, by direct cooling (DC) of aluminum alloys and casting into ingot forms, novel alloys can be prepared into forged forms and are appropriately tempered. After conventional scalping, lathing or peeling (if necessary) and homogenization, these ingots can be further processed by hot working the product, and homogenization can be completed before or after scalping. The product can then be optionally cold worked and / or optionally annealed. After any cold work and any annealing (which can be performed multiple times and in any order), the product can then be solution heat treated, quenched, such as quenched in gas (e.g., air) or liquid (e.g., water) or in both and reach an appropriate temperature (e.g., quenched to ambient temperature), then natural and / or artificial aging.
[0036] In one method, a new 7xxx product aluminum alloy product is processed to one of an F, W or T temper, wherein the processing includes hot rolling the 7xxx aluminum alloy product to one of an intermediate specification and a final specification. In one embodiment, the hot rolling includes (a) a first rolling along a first direction and (b) a second rolling along a second direction. In one embodiment, the first direction is one of a longitudinal and a transverse direction, and the second direction is offset from the first direction by 45° to 90°. It has been surprisingly found that hot rolling along at least two directions can promote one or more of the improved properties described herein.
[0037] The new 7xxx aluminum alloy product can have any suitable final specification thickness. In one embodiment, the new 7xxx aluminum alloy is in the form of a thick forged product. The thick forged aluminum alloy product is a forged product with a cross-sectional thickness of at least 50.8 mm (2 inches). The improved properties described herein can be achieved with a thick forged product with a thickness of up to 305 mm (12 inches). The forged product can be a rolled product, a forged product, or an extruded product. In one embodiment, the new 7xxx aluminum alloy product has a thickness of at least 76.2 mm (3 inches). In another embodiment, the new 7xxx aluminum alloy product has a thickness of at least 101.6 mm (4 inches). In yet another embodiment, the new 7xxx aluminum alloy product has a thickness of at least 127 mm (5 inches). In another embodiment, the new 7xxx aluminum alloy product has a thickness of at least 152.4 mm (6 inches). In yet another embodiment, the new 7xxx aluminum alloy product has a thickness of at least 177.8 mm (7 inches). In another embodiment, the new 7xxx aluminum alloy product has a thickness of at least 203.2 mm (8 inches). In yet another embodiment, the new 7xxx aluminum alloy product has a thickness of at least 228.6 mm (9 inches). In another embodiment, the new 7xxx aluminum alloy product has a thickness of 177.8 to 254 mm (7 to 10 inches).
[0038] iii. Microstructure
[0039] As discussed above, the new 7xxx aluminum alloy products can achieve unique microstructures that may, at least in part, give rise to the unique properties shown herein. For example, as described below, Recrystallization Assay Procedure As determined herein, the 7xxx aluminum alloy may be partially recrystallized, having 10 vol % to 40 vol % recrystallized grains. Recrystallization Determination procedureThe fully unrecrystallized product contains less than 10% recrystallized grains as determined. The partially recrystallized product contains between 10% and 90% recrystallized grains. The fully recrystallized product contains over 90% recrystallized grains. The partially recrystallized product having between 10% and 40% by volume of recrystallized grains is within the preferred amount of recrystallization, but any partially recrystallized 7xxx aluminum alloy product may be within the scope of the present disclosure if it achieves the properties described herein.
[0040] In one approach, the new 7xxx aluminum alloy product is a partially recrystallized product having 10% to 40% by volume of recrystallized grains. In one embodiment, the partially recrystallized 7xxx aluminum alloy product includes at least 12.5% by volume of recrystallized grains. In another embodiment, the partially recrystallized 7xxx aluminum alloy product includes at least 15% by volume of recrystallized grains. In yet another embodiment, the partially recrystallized 7xxx aluminum alloy product includes at least 17.5% by volume of recrystallized grains. In another embodiment, the partially recrystallized 7xxx aluminum alloy product includes at least 20% by volume of recrystallized grains. In one embodiment, the partially recrystallized 7xxx aluminum alloy product includes no more than 37.5% by volume of recrystallized grains. In another embodiment, the partially recrystallized 7xxx aluminum alloy product includes no more than 35% by volume of recrystallized grains. In yet another embodiment, the partially recrystallized 7xxx aluminum alloy product includes no more than 32.5% by volume of recrystallized grains. In another embodiment, the partially recrystallized 7xxx aluminum alloy product includes no more than 30% by volume of recrystallized grains.
[0041] As described above, in one embodiment, a partially recrystallized product may be produced by: (i) using no more than 0.11 wt. % Zr (or other anti-recrystallization agent) in a 7xxx aluminum alloy product; (ii) particle stimulated nucleation; or (iii) both. Because particle stimulated nucleation (PSN) is involved, the new 7xxx aluminum alloy may include a sufficient amount of second phase particles to promote PSN. When the 7xxx aluminum alloy is processed into a suitable wrought product form, recrystallization through PSN may occur if suitable conditions and a certain amount of second phase particles are present during the plastic deformation of the 7xxx aluminum alloy.
[0042] In some embodiments, at least some of the recrystallized grains are located around the periphery of the non-recrystallized grains. For example, one or more recrystallized grains may partially or completely surround at least some of the non-recrystallized grains. In one embodiment, at least some of the recrystallized grains only partially surround at least some of the non-recrystallized grains.
[0043] As described above, the new 7xxx aluminum alloy product can achieve an average grain size (d-bin) of at least 300 microns, wherein the average grain size is the area-weighted average circular equivalent diameter grain size. Grain size is measured according to the microstructure evaluation procedure described below. In one embodiment, the new 7xxx aluminum alloy product can achieve an average grain size (d-bin) of at least 350 microns. In another embodiment, the new 7xxx aluminum alloy product can achieve an average grain size (d-bin) of at least 400 microns. In yet another embodiment, the new 7xxx aluminum alloy product can achieve an average grain size (d-bin) of at least 450 microns. In another embodiment, the new 7xxx aluminum alloy product can achieve an average grain size (d-bin) of at least 500 microns.
[0044] As described above, relative to the average grain size of the new 7xxx aluminum alloy product, the new 7xxx aluminum alloy product may include a customized amount of recrystallized regions. In one embodiment, the new 7xxx aluminum alloy product achieves an ID: d-bar ratio of 0.5 to 2.0, wherein the ID: d-bar ratio is the ratio of (A) average intercept (ID) to (B) average grain size (d-bar) of the 7xxx aluminum alloy product. For the purpose of calculating this ratio, the average intercept (ID) is the average distance between the recrystallized regions of the 7xxx aluminum alloy product, and will be determined according to the microstructure evaluation procedure described below. In one embodiment, the new 7xxx aluminum alloy product achieves an ID of at least 0.6: d-bar ratio. In another embodiment, the new 7xxx aluminum alloy product achieves an ID of at least 0.7: d-bar ratio. In yet another embodiment, the new 7xxx aluminum alloy product achieves an ID of at least 0.8: d-bar ratio. In another embodiment, the new 7xxx aluminum alloy product achieves an ID of at least 0.9: d-bar ratio. In yet another embodiment, the new 7xxx aluminum alloy product achieves an ID of at least 1.0: d-bar ratio.
[0045] In one embodiment, the new 7xxx aluminum alloy product achieves an ID:d-bar ratio of no more than 1.9. In another embodiment, the new 7xxx aluminum alloy product achieves an ID:d-bar ratio of no more than 1.8. In yet another embodiment, the new 7xxx aluminum alloy product achieves an ID:d-bar ratio of no more than 1.7. In another embodiment, the new 7xxx aluminum alloy product achieves an ID:d-bar ratio of no more than 1.6. In yet another embodiment, the new 7xxx aluminum alloy product achieves an ID:d-bar ratio of no more than 1.5. In another embodiment, the new 7xxx aluminum alloy product achieves an ID:d-bar ratio of no more than 1.4. In yet another embodiment, the new 7xxx aluminum alloy product achieves an ID:d-bar ratio of no more than 1.35. In another embodiment, the new 7xxx aluminum alloy product achieves an ID:d-bar ratio of no more than 1.3. In yet another embodiment, the new 7xxx aluminum alloy product achieves an ID:d-bar ratio of no more than 1.25.
[0046] iv. characteristic
[0047] As noted above, the new 7xxx aluminum alloy products described herein may achieve improved combinations of properties, such as improved combinations of two or more of strength, ductility, and fracture toughness.
[0048] In one embodiment, a new 7xxx aluminum alloy product realizes improved properties at equivalent longitudinal strength over a compositionally equivalent aluminum alloy, where the compositionally equivalent alloy is fully unrecrystallized.
[0049] A compositionally equivalent aluminum alloy is a 7xxx aluminum alloy containing “equivalent amounts” of Zn, Cu, Mg, Mn, Cr, V, Ti, Fe, and Si as the 7xxx aluminum alloy product, but includes 0.11 wt. % to 0.13 wt. % Zr. “Equivalent amounts” means that all of Zn, Cu, Mg are each within 3% of the composition of the new 7xxx aluminum alloy product, and all of Mn, Cr, V, Fe, and Si are each within + / - 0.02 wt. % of the new 7xxx aluminum alloy product, and Ti is always between 0.015 wt. % and 0.025 wt. %. For example, if a new 7xxx aluminum alloy product includes 6.67 wt % Zn, 2.03 wt % Mg, 1.79 wt % Cu, 0.07 wt % Zr, 0.25 wt % Mn, 0.01 wt % Cr, 0.01 wt % V, 0.020 wt % Ti, 0.10 wt % Fe, and 0.06 wt % Si, then the compositionally equivalent aluminum alloy must have 6.47 wt % to 6.87 wt % Zn (i.e., 6.67 wt % Zn±3%), 1.96 wt % to 2.09 wt % Mg (i.e., 2.03 wt % Mg±3%), 1.74 wt % to 1.84 wt % Cu (i.e., 1.79 wt % Cu±3%), 0.11 wt % to 0.63 wt % Sr (i.e., 0.11 wt % to 0.63 wt % Sr). 13 wt% Zr (according to 0.11 wt% to 0.13 wt% Zr requirement), 0.23 wt% to 0.27 wt% Mn (i.e., 0.25 wt% Mn±0.02 wt%), 0 wt% to 0.03 wt% Cr (i.e., 0.01 wt% Cr±0.02 wt%), 0 wt% to 0.03 wt% V (i.e., 0.01 wt% V±0.02 wt%), 0.015 wt% to 0.025 wt% Ti (according to Ti requirement), 0.08 wt% to 0.12 wt% Fe (i.e., 0.10 wt% Fe±0.02 wt%) and 0.04 wt% to 0.08 wt% Si (i.e., 0.06 wt% Si±0.02 wt%).
[0050] • Compositionally equivalent aluminum alloys must have specifications (thickness) equivalent to 7xxx aluminum alloy products, where the specifications of the products are within the standard tolerances of each other provided in ANSI H35.2 (2009).
[0051] “Equivalent longitudinal strength” means that the TYS-L achieved by a 7xxx aluminum alloy product is no more than 10 MPa lower than the TYS-L of an equivalent aluminum alloy of the composition.
[0052] In one method, the improved property is selected from LT elongation, ST elongation, TL K IC Fracture toughness, SL K ICThese improvements may be realized in any wrought product form, but may be particularly applicable to thick plate products having the microstructural features described herein.
[0053] In one embodiment, the improved property is at least a LT elongation property, wherein the new 7xxx aluminum alloy product achieves at least 1% higher LT elongation compared to the LT elongation of a compositionally equivalent aluminum alloy. In another embodiment, the new 7xxx aluminum alloy product achieves at least 2% higher LT elongation compared to the LT elongation of a compositionally equivalent aluminum alloy. In yet another embodiment, the new 7xxx aluminum alloy product achieves at least 3% higher LT elongation compared to a compositionally equivalent aluminum alloy. In another embodiment, the new 7xxx aluminum alloy product achieves at least 4% higher LT elongation compared to a compositionally equivalent aluminum alloy. In yet another embodiment, the new 7xxx aluminum alloy product achieves at least 5% higher LT elongation compared to a compositionally equivalent aluminum alloy. In another embodiment, the new 7xxx aluminum alloy product achieves at least 6% higher LT elongation compared to a compositionally equivalent aluminum alloy. In yet another embodiment, the new 7xxx aluminum alloy product achieves at least 7% higher LT elongation compared to a compositionally equivalent aluminum alloy. In another embodiment, the new 7xxx aluminum alloy product achieves at least 8% higher LT elongation compared to a compositionally equivalent aluminum alloy. In yet another embodiment, the new 7xxx aluminum alloy product achieves at least 9% higher LT elongation compared to a compositionally equivalent aluminum alloy. In another embodiment, the new 7xxx aluminum alloy product achieves at least 10% higher LT elongation compared to a compositionally equivalent aluminum alloy. In yet another embodiment, the new 7xxx aluminum alloy product achieves at least 15% higher LT elongation compared to a compositionally equivalent aluminum alloy. In another embodiment, the new 7xxx aluminum alloy product achieves at least 20% higher LT elongation compared to a compositionally equivalent aluminum alloy. In yet another embodiment, the new 7xxx aluminum alloy product achieves at least 25% higher LT elongation compared to a compositionally equivalent aluminum alloy. In another embodiment, the new 7xxx aluminum alloy product achieves at least 30% higher LT elongation compared to a compositionally equivalent aluminum alloy. In yet another embodiment, the new 7xxx aluminum alloy product achieves at least 35% higher LT elongation compared to a compositionally equivalent aluminum alloy. In another embodiment, the new 7xxx aluminum alloy product achieves at least 40% higher LT elongation compared to a compositionally equivalent aluminum alloy.
[0054] “Higher LT elongation” is calculated as: [(LT elongation of new 7xxx aluminum alloy) / (LT elongation of compositionally equivalent aluminum alloy)]-1]*100%.
[0055] In one embodiment, the improved property is at least a TL fracture toughness property, wherein the new 7xxx aluminum alloy product realizes at least 1% higher TL K compared to a compositionally equivalent aluminum alloy. IC In another embodiment, a new 7xxx aluminum alloy product realizes at least 2% higher TL K compared to a compositionally equivalent aluminum alloy. IC In yet another embodiment, a new 7xxx aluminum alloy product achieves at least 3% higher TL K compared to a compositionally equivalent aluminum alloy. IC In another embodiment, a new 7xxx aluminum alloy product realizes at least 4% higher TL K compared to a compositionally equivalent aluminum alloy. IC In another embodiment, a new 7xxx aluminum alloy product realizes at least 5% higher T-LK than a compositionally equivalent aluminum alloy. IC characteristic.
[0056] "Higher TL K IC The calculation formula is: [(New 7xxx aluminum alloy TL K IC ) / (composition equivalent aluminum alloy TL K IC )]-1]*100%.
[0057] In one embodiment, the improved property is at least an ST elongation property, wherein the new 7xxx aluminum alloy product achieves at least 1% higher ST elongation compared to a compositionally equivalent aluminum alloy. In another embodiment, the new 7xxx aluminum alloy product achieves at least 2% higher ST elongation compared to a compositionally equivalent aluminum alloy. In yet another embodiment, the new 7xxx aluminum alloy product achieves at least 3% higher ST elongation compared to a compositionally equivalent aluminum alloy. In another embodiment, the new 7xxx aluminum alloy product achieves at least 4% higher ST elongation. In yet another embodiment, the new 7xxx aluminum alloy product achieves at least 5% higher ST elongation compared to a compositionally equivalent aluminum alloy. In another embodiment, the new 7xxx aluminum alloy product achieves at least 6% higher ST elongation compared to a compositionally equivalent aluminum alloy. In yet another embodiment, the new 7xxx aluminum alloy product achieves at least 7% higher ST elongation compared to a compositionally equivalent aluminum alloy. In another embodiment, the new 7xxx aluminum alloy product achieves at least 8% higher ST elongation compared to a compositionally equivalent aluminum alloy. In yet another embodiment, the new 7xxx aluminum alloy product achieves at least 9% higher ST elongation compared to a compositionally equivalent aluminum alloy. In another embodiment, the new 7xxx aluminum alloy product achieves at least 10% higher ST elongation compared to a compositionally equivalent aluminum alloy. In yet another embodiment, the new 7xxx aluminum alloy product achieves at least 15% higher ST elongation compared to a compositionally equivalent aluminum alloy. In another embodiment, the new 7xxx aluminum alloy product achieves at least 20% higher ST elongation compared to a compositionally equivalent aluminum alloy.
[0058] “Higher ST elongation” is calculated as: [(ST elongation of new 7xxx aluminum alloy) / (ST elongation of compositionally equivalent aluminum alloy)]-1]*100%.
[0059] In one embodiment, the improved property is at least a SL fracture toughness property, wherein the new 7xxx aluminum alloy products realize at least 1% higher SL K compared to a compositionally equivalent aluminum alloy. IC In another embodiment, a new 7xxx aluminum alloy product realizes at least 2% higher SL K compared to a compositionally equivalent aluminum alloy. IC In yet another embodiment, a new 7xxx aluminum alloy product realizes at least 3% higher SL K compared to a compositionally equivalent aluminum alloy. IC In another embodiment, a new 7xxx aluminum alloy product realizes at least 4% higher SL K compared to a compositionally equivalent aluminum alloy. IC In another embodiment, a new 7xxx aluminum alloy product realizes at least 5% higher SL K compared to a compositionally equivalent aluminum alloy. IC characteristic.
[0060] · "Higher SL K IC The calculation formula is: [(New 7xxx aluminum alloy SL K IC ) / (composition equivalent aluminum alloy SL K IC )]-1]*100%.
[0061] In one embodiment, a new 7xxx aluminum alloy product realizes higher LT elongation, higher ST elongation, higher TL K IC and higher SL K IC In another embodiment, a new 7xxx aluminum alloy product realizes higher LT elongation, higher ST elongation, higher TL K IC and higher SL K IC In yet another embodiment, a new 7xxx aluminum alloy product achieves higher LT elongation, higher ST elongation, higher TL K IC and higher SL K IC These improvements may be realized in any wrought product form, but may be particularly applicable to thick plate products having the microstructural features described herein.
[0062] In one approach, the new 7xxx aluminum alloy product has a composition consistent with AA7050, wherein the AA7050 consistent alloy may include 0 wt. % to 0.11 wt. % Zr, and the compositionally equivalent aluminum alloy is a standard AA7050 alloy having 0.11 wt. % to 0.13 wt. % Zr. In one embodiment, the AA7050 consistent alloy achieves higher LT elongation, higher ST elongation, higher TL K compared to the standard AA7050 alloy at equivalent longitudinal strength. IC and higher SL K IC In another embodiment, the AA7050 conforming alloy achieves higher LT elongation, higher ST elongation, higher TL K compared to the standard AA7050 alloy at equivalent longitudinal strength. IC and higher SL K IC In yet another embodiment, the AA7050 conforming alloy achieves higher LT elongation, higher ST elongation, higher TL K IC and higher SL K ICIn another embodiment, the AA7050 conforming alloy achieves higher LT elongation, higher ST elongation, higher TL K IC and higher SL K IC These improvements may be realized in any wrought product form suitable for AA7050, but may be particularly applicable to thick plate AA7050 products having the microstructural features described herein.
[0063] v. Application
[0064] The new aluminum alloys described herein can be used in a variety of product applications, such as aerospace applications. For example, the new alloys can be used as wing ribs, spars, frames (thick and thin), sides of fuselage fittings / attachments, large pieces / lugs, bulkheads, single-piece / built cargo compartment floor structures, and landing gear / pylon / engine support structures for aircraft / aerospace vehicles. The new alloys can also be used as armor products, such as armored vehicles, etc.
[0065] vi. definition
[0066] The “wrought aluminum alloy product” refers to an aluminum alloy product that is hot-worked after casting, and includes rolled products (sheets or plates), forged products, and extruded products.
[0067] "Hot working" such as hot rolling refers to working an aluminum alloy product at elevated temperatures, and generally at least 121.1°C (250°F). Strain hardening is limited / avoided during hot working, which generally distinguishes hot working from cold working.
[0068] "Cold working" such as cold rolling refers to working an aluminum alloy product at temperatures that are not considered hot working temperatures, generally below about 121.1°C (250°F), such as at ambient temperature.
[0069] Temper definitions are in accordance with ANSI H35.1 (2009) published by The Aluminum Association, entitled "American National Standard Alloy and Temper Designation Systems for Aluminum."
[0070] Strength and elongation were measured according to ASTM E8 / E8M-21 and B557-15. Fracture toughness was measured according to ASTM E399-20a and B645-21.
[0071] vii. Microstructural Evaluation Procedure
[0072] The following procedures and definitions apply to measuring microstructural characteristics (eg, percent recrystallization, grain size, grain intercept) of products manufactured according to the present patent application.
[0073] The term “grain” has the meaning defined in ASTM E2627-13 (2019) §3.1.6, namely, “a group of similarly oriented adjacent points on a scanned grid. The group is surrounded by a perimeter, and the misorientation across the perimeter exceeds a specified tolerance value.”
[0074] The "Grain Size" is calculated by the following equation:
[0075]
[0076] ·A i is the area of a single grain measured using the commercial software OIM Analysis Software (version 8.5.1) or equivalent according to ASTM E2627-13 (2019) equation (1); and
[0077] · Among them d i is the calculated individual grain size assuming the grains are round.
[0078] The "area-weighted average grain size" is calculated by the following equation:
[0079]
[0080] ·A i is the area of each individual grain measured using the commercial software OIM Analysis Software (version 8.5.1) or equivalent;
[0081] · Among them d i is the calculated individual grain size assuming the grains are round; and
[0082] Where d-bar is the area-weighted average grain size.
[0083] "Average intercept" refers to the average distance between recrystallized grains (sometimes referred to herein as "first grains") as determined by ASTM E112-13 (2021) §17.6 and E1382-97 (2015) §13.7.5. Here, the chord length measured is not the distance between grain boundaries, but the distance between recrystallized regions. In addition, the "parallel straight test lines" are not randomly applied, but are aligned with the rolling or longitudinal direction (L) to determine the distribution along that particular axis. The average intercept (ID) was measured using the commercial image analysis software MIPAR (version 3.3.4).
[0084] "Recrystallized percentage" and the like refer to the volume percentage of the wrought aluminum alloy product having recrystallized grains. Recrystallization Assay Procedure , the amount of recrystallized grains is determined by performing EBSD (electron backscatter diffraction) analysis on an appropriate area of a wrought aluminum alloy product. Generally, the measured area should be uniform and represent the bulk volume analyzed. As stated in ASTM standards (E112, E930, E1181), the accuracy will increase with the number of grains measured. According to ASTM E2627-13 (2019) §12.4, the measured area should contain at least 500 grains.
[0085] a. Recrystallization Assay Procedure
[0086] "Recrystallized grains" refer to crystal microstructural grains that meet the "first grain criteria" defined below, as measured using the electron backscatter diffraction (EBSD) sampling procedure described below.
[0087] EBSD analysis will be done on a confined volume of the plate, specifically T / 4 on the L-ST plane (defined as 25% of the distance from the plate surface), using the EBSD sample procedure below. The size of the sample to be analyzed will generally vary depending on the specification; for thinner plates, it may be necessary to limit the ST size to avoid microstructural heterogeneities. Before measurement, the EBSD sample is prepared by standard metallographic sample preparation methods. For example, the EBSD sample is metallographically prepared and then polished (e.g., using 0.05 micron colloidal silica). The sample is then etched by immersion in a solution of 0.5% hydrofluoric acid HF solution for 5 seconds, then rinsed and dried.
[0088] The "EBSD Sample Program" is as follows:
[0089] The software used was APEX EBSD Collection Software (Version 2) (EDAX Inc., New Jersey, USA) or equivalent, connected to a Velocity SuperEBSD camera (EDAX Inc., New Jersey, USA) or equivalent. The scanning electron microscope (SEM) was the APREO S Field Emission Gun (Thermo Fisher Scientific. Waltham, MA, USA) or equivalent.
[0090] The SEM operating parameters for the EBSD scan were: an accelerating voltage of 20 kV, a beam current of 51 nA (nanoampere), a working distance of 18 mm, a 68° stage tilt, and dynamic focus was enabled. The acquisition mode was a composite scan consisting of multiple maps with individual map dimensions offset in the x- and y-axes so that there was no overlap; points were collected using a square grid. Selection was made so that orientation was acquired in the analysis (i.e., no Hough peak data was acquired). An SEM magnification of 120x was used, with individual frame dimensions of 1.0 mm on each side (x- and y-axes); the total composite area was typically greater than 18 mm for L and greater than 12 mm for ST. More than 13 million data points were generated using a 4.0 μm step size. Different grain sizes may be used, depending on the specification. The acquired data was exported in the form of an *.osc file. This data can be used to calculate the volume fraction of the first type of grains, as described below.
[0091] · Calculation of the volume fraction of the first type of grains : The volume fraction of the first type of grains is calculated using the *.osc file and data from OIM Analysis Software (Version 8.5.1) (EDAX, Inc., New Jersey, USA) or equivalent. Prior to the calculation, a two-step data cleanup can be performed. First, for any point with a confidence index (CI) below a threshold of 0.1, a neighbor orientation correlation cleanup is performed, requiring a minimum of five (5) neighbors to have consistent orientations. Second, a grain expansion cleanup is performed for any point with CI ≤ 0.2 and any grain size less than 5 data points. The amount of the first type of grains is then calculated by the software using the first grain standard (as follows).
[0092] · First Die Standard : Calculates the grain orientation distribution (GOS). All "Apply partitions before calculation", "Include edge grains" and "Ignore twin boundary definition" should be required; a grain should contain a minimum of 5 points. Any grain with GAM ≤ 2.5° is a first type grain.
[0093] "First grain volume" (FGV) refers to the volume fraction of a first type of grains of a crystalline material.
[0094] The "recrystallization percentage" (ReX%) is determined by the following formula: FGV*100%.
[0095] viii. other
[0096] These and other aspects, advantages, and novel features of the new technology are set forth in part in the following description and will become apparent to those skilled in the art upon examination of the following description and the accompanying drawings, or may be learned by practicing one or more embodiments of the technology provided by the present disclosure.
[0097] Among those benefits and improvements that have been disclosed, other objects and advantages of the present invention will become apparent from the following description in conjunction with the accompanying drawings. Detailed embodiments of the present invention are disclosed herein; however, it should be understood that the disclosed embodiments are merely illustrative of the present invention that can be embodied in various forms. In addition, each example given together with the various embodiments of the present invention is intended to be illustrative rather than limiting.
[0098] Throughout the specification and claims, unless the context clearly states otherwise, the following terms take the meanings explicitly associated herein. As used herein, the phrases "in one embodiment" and "in some embodiments" do not necessarily refer to the same embodiment, although they may be. In addition, as used herein, the phrases "in another embodiment" and "in some other embodiments" do not necessarily refer to different embodiments, although they may be. Therefore, the various embodiments of the present invention can be easily combined without departing from the scope or spirit of the present invention.
[0099] Additionally, as used herein, the term "or" is an inclusive "or" operator and is equivalent to the term "and / or" unless the context clearly indicates otherwise. The term "based on" is not exclusive and allows for being based on additional factors that are not described, unless the context clearly indicates otherwise. Additionally, throughout this specification, "a" refers to a combination of "based on" and "based on" unless the context clearly indicates otherwise.
[0100] The meanings of "a", "an" and "the" include plural referents. Unless the context clearly dictates otherwise, the meaning of "in" includes "in" and "on".
[0101] Although multiple embodiments of the present invention have been described, it should be understood that these embodiments are illustrative only and non-restrictive, and that various modifications may be apparent to those skilled in the art. Furthermore, unless the context clearly requires otherwise, the various steps may be performed in any desired order, and any applicable steps may be added and / or eliminated. DETAILED DESCRIPTION
[0102] Example 1
[0103] Several different AA7050 materials were produced, the compositions of which are shown below.
[0104] Table 1 - Composition of Example 1 alloy (weight %) *
[0105]
[0106] *The balance of the alloy is incidental elements and impurities, wherein the alloy contains not more than 0.03% by weight of any one impurity and wherein the total percentage of all impurities contained in the alloy does not exceed 0.10% by weight.
[0107] AA7050 alloys 1-3 and 7-8 have 0.08 wt % Zr and are alloys of the present invention. AA7050 alloys 4-6 and 9-11 have 0.11 wt % Zr and are not alloys of the present invention.
[0108] To produce the material, the ingots were conventionally shaped / stripped, homogenized, and then rolled to a final gauge of 220 mm (8.7 inches) or 170 mm (6.7 inches). The plates were then solution heat treated, then cold water quenched, then stretched, then naturally aged for at least 72 hours, and then artificially aged to a T7451 temper. The mechanical properties of the material are shown in Tables 2a to 2c below. Table 4 below shows the microscopy data. The recrystallization percentage, grain size, and intercept were determined according to the microstructure evaluation procedures contained herein.
[0109] Table 2a - Mechanical properties data (L)
[0110]
[0111] Table 2b - Mechanical properties data (LT)
[0112]
[0113]
[0114] Table 2c-Mechanical properties data (ST)
[0115]
[0116] Tables 3a to 3c below compare the average inventive properties with the average non-inventive properties for two specifications of alloy.
[0117] Table 3a – Comparison of mechanical properties (L)
[0118]
[0119] Table 3b - Mechanical properties comparison (LT)
[0120]
[0121] Table 3c - Mechanical properties comparison (ST)
[0122]
[0123] As shown, the invention alloys generally achieve similar or slightly worse performance in the L direction. This is more than offset by the improvements in elongation and fracture toughness in the LT and ST directions and at substantially similar strengths.
[0124] Table 4 - Microscope Data*
[0125]
[0126] *Note: For samples 7-11, the scanned area was slightly smaller than that provided in the microstructure evaluation program; if a full area scan had been completed, the data are still considered representative of what would be expected for recrystallization, grain size, and intercept, but may have had higher standard deviation values.
[0127] As shown in the microscopy data, the inventive alloy is partially recrystallized and achieves much smaller distances between recrystallized regions than the non-inventive alloy. The grain size is also much smaller. The ratio of the average intercept to the average grain size is also significantly different.
[0128] While the unexpected improvements demonstrated above are relative to a partially recrystallized AA7050 product, it is contemplated that such unexpected improvements may be achieved in other 7xxx aluminum alloy products, including those described herein.
[0129] Although various embodiments of the present disclosure have been described in detail, it is obvious that those skilled in the art will modify and adjust these embodiments. However, it should be clearly understood that such modifications and adjustments are within the spirit and scope of the present disclosure.
Claims
1. A 7xxx aluminum alloy sheet product, wherein the 7xxx aluminum alloy sheet product comprises: (a) 5 to 10 wt % Zn, 1 to 3 wt % Mg and 1 to 3 wt % Cu; (a) At least 2 inches in thickness; (b) 10% to 40% recrystallized grains; (c) an average grain size (d-bar) of at least 300 micrometers, wherein the average grain size is the area-weighted average circular equivalent diameter grain size; and (d) an ID:d-bar ratio of 0.5 to 2.0, wherein the ID:d-bar ratio is the ratio of (A) the average intercept (ID) to (B) the average grain size (d-bar) of the 7xxx aluminum alloy sheet product; wherein the average intercept (ID) is the average distance between recrystallized regions of the 7xxx aluminum alloy sheet product; wherein at least some of the recrystallized grains are located at the periphery of the non-recrystallized grains; and wherein the recrystallized grains are achieved at least in part due to: (i) using no more than 0.11 wt. % Zr in the 7xxx aluminum alloy sheet product; (ii) particle stimulated nucleation; or (iii) both.
2. The 7xxx aluminum alloy sheet product of claim 1, wherein the 7xxx aluminum alloy sheet product comprises no more than 0.10 wt. % Zr, or no more than 0.09 wt. % Zr, or no more than 0.08 wt. % Zr, or no more than 0.07 wt. % Zr.
3. The 7xxx aluminum alloy sheet product of claim 1, wherein the 7xxx aluminum alloy sheet product comprises at least 0.03 wt. % Zr, or at least 0.04 wt. % Zr, or at least 0.05 wt. % Zr, or at least 0.06 wt. % Zr.
4. The 7xxx aluminum alloy sheet product of any one of the preceding claims, wherein the 7xxx aluminum alloy sheet product has a thickness of at least 3 inches, or at least 4 inches, or at least 5 inches, or at least 6 inches, or at least 7 inches, or at least 8 inches, or at least 9 inches.
5. The 7xxx aluminum alloy sheet product of any one of the preceding claims, wherein the 7xxx aluminum alloy sheet product has a thickness no greater than 12 inches.
6. The 7xxx aluminum alloy sheet product of any one of the preceding claims, wherein the 7xxx aluminum alloy sheet product comprises at least 12.5% recrystallized grains, or at least 15% recrystallized grains, or at least 17.5% recrystallized grains, or at least 20% recrystallized grains.
7. The 7xxx aluminum alloy sheet product of any one of the preceding claims, wherein the 7xxx aluminum alloy sheet product comprises no more than 37.5% recrystallized grains, or no more than 35% recrystallized grains, or no more than 32.5% recrystallized grains, or no more than 30% recrystallized grains.
8. The 7xxx aluminum alloy sheet product of any one of the preceding claims, wherein the average grain size is at least 350 microns, or at least 400 microns, or at least 450 microns, or at least 500 microns.
9. The 7xxx aluminum alloy sheet product of any one of the preceding claims, wherein the ID:d-bar ratio is at least 0.6, or at least 0.7, or at least 0.8, or at least 0.9, or at least 1.
0.
10. The 7xxx aluminum alloy sheet product of any one of the preceding claims, wherein the ID:d-bar ratio is no more than 1.9, or no more than 1.8, or no more than 1.7, or no more than 1.6, or no more than 1.5, or no more than 1.4, or no more than 1.35, or no more than 1.3, or no more than 1.
25.
11. The 7xxx aluminum alloy sheet product of any of the preceding claims, wherein the 7xxx aluminum alloy sheet product achieves improved properties over compositionally equivalent aluminum alloy sheet products at equivalent longitudinal strength; wherein the compositionally equivalent aluminum alloy sheet product comprises 0.11 wt. % to 0.13 wt. % Zr, and wherein the compositionally equivalent aluminum alloy sheet product has an equivalent specification to the 7xxx aluminum alloy sheet product; wherein the improved properties are selected from the group consisting of: LT elongation, ST elongation, TL K IC Fracture toughness, S-LK IC Fracture toughness and its combinations; Wherein the equivalent longitudinal strength is that the TYS-L achieved by the 7xxx aluminum alloy plate product is no more than 10 MPa lower than the TYS-L of the compositionally equivalent aluminum alloy plate product.
12. The 7xxx aluminum alloy sheet product of claim 11, wherein the improved property is a LT elongation property, wherein the 7xxx aluminum alloy sheet product realizes at least 1% higher LT elongation, or at least 2% higher LT elongation, or at least 3% higher LT elongation, or at least 4% higher LT elongation, or at least 5% higher LT elongation, or at least 6% higher LT elongation, or at least 7% higher LT elongation, or at least 8% higher LT elongation, or at least 9% higher LT elongation, or at least 10% higher LT elongation, or at least 15% higher LT elongation, or at least 20% higher LT elongation, or at least 25% higher LT elongation, or at least 30% higher LT elongation, or at least 35% higher LT elongation, or at least 40% higher LT elongation; The higher LT elongation is calculated as: [(the 7xxx aluminum alloy plate LT elongation) / (the compositionally equivalent aluminum alloy plate LT elongation)] - 1]*100%.
13. The 7xxx aluminum alloy sheet product of any one of claims 11 to 12, wherein the improved property is T-LK IC characteristics, wherein the 7xxx aluminum alloy sheet product achieves at least 1% higher TL K IC characteristics, or at least 2% higher TL K IC characteristics, or at least 3% higher T-LK IC characteristics, or at least 4% higher TL K IC characteristics, or at least 5% higher TL K IC characteristic; The higher TL K IC The properties are calculated as follows: [(the 7xxx aluminum alloy plate TL K IC ) / (the composition equivalent aluminum alloy plate TL K IC )]–1]*100%.
14. The 7xxx aluminum alloy sheet product of any one of claims 11 to 13, wherein the improved property is an ST elongation property, wherein the 7xxx aluminum alloy sheet product realizes at least 1% higher ST elongation, or at least 2% higher ST elongation, or at least 3% higher ST elongation, or at least 4% higher ST elongation, or at least 5% higher ST elongation, or at least 6% higher ST elongation, or at least 7% higher ST elongation, or at least 8% higher ST elongation, or at least 9% higher ST elongation, or at least 10% higher ST elongation, or at least 15% higher ST elongation, or at least 20% higher ST elongation; The higher ST elongation is calculated as: [(the 7xxx aluminum alloy plate ST elongation) / (the compositionally equivalent aluminum alloy plate ST elongation)] - 1]*100%.
15. The 7xxx aluminum alloy sheet product of any one of claims 11 to 14, wherein the improved property is S-LK IC characteristics, wherein the 7xxx aluminum alloy sheet product achieves at least 1% higher SL K IC characteristics, or at least 2% higher SL K IC characteristics, or at least 3% higher S-LK IC characteristics, or at least 4% higher SL K IC characteristics, or at least 5% higher SL K IC characteristics, or at least 6% higher SL K IC characteristics, or at least 7% higher SL K IC characteristics, or at least 8% higher SL K IC characteristics, or at least 9% higher SL K IC characteristics, or at least 2% higher S-LK IC characteristics, or at least 10% higher SL K IC characteristics, or at least 11% higher SL K IC characteristics, or at least 12% higher SL K IC characteristic; The higher SL K IC The properties are calculated as follows: [(the 7xxx aluminum alloy plate SL K IC ) / (the composition equivalent aluminum alloy plate SL K IC )]–1]*100%.
16. The 7xxx aluminum alloy sheet product of any one of the preceding claims, wherein the 7xxx aluminum alloy has a composition consistent with AA7050, wherein the AA7050 consistent alloy may include 0 wt. % to 0.11 wt. % Zr.
17. The 7xxx aluminum alloy sheet product of any one of the preceding claims, wherein the 7xxx aluminum alloy sheet product is processed to one of an F, W, or T temper, wherein the processing comprises hot rolling the 7xxx aluminum alloy product to one of an intermediate gauge and a final gauge, wherein the hot rolling comprises: (a) a first rolling along a first direction; (b) a second rolling along a second direction; wherein the first direction is one of the longitudinal direction and the transverse direction; and The second direction is offset from the first direction by 45° to 90°.
Citation Information
Patent Citations
Thick wrought 7xxx aluminum alloys, and methods for making the same
US20170088920A1
Thick wrought 7xxx aluminum alloys, and methods for making the same
US20200115780A1
7xxx aluminum alloys
US20210340656A1
Improved thick wrought 7xxx aluminum alloys, and methods for making the same
US20220106672A1
Thick products made of heat-treatable aluminum alloy with improved toughness and process for manufacturing these products
US7135077B2